Relationship between Process Conditions and Seam Weld width in Extruded Shapes through a Porthole Die with Customized Geometry. (2015) - Gagliardi, F.; Citrea, T.; Ambrogio, G.; Filice, L.; Misiolek, W.Z.
Abstract: Extrusion porthole die plays an important role in hollow profile manufacturing of light alloys. The reliability of extruded parts is strongly affected by the quality of extrusion longitudinal seam welds. In the proposed work, a special test die was designed and manufactured with three mandrel supporting legs, each one of a different width. The extruded billet is split into three metal streams, all of the same cross section geometry; however, the legs are not symmetrically positioned. Experimental and numerical campaigns were carried out to analyze the influence of the leg size, ram speed and extrusion ratio on the welding line width.